Design and Accuracy Test of Digital Body Circumference Measurement: Perancangan Dan Uji Akurasi Alat Ukur Lingkar Tubuh Digital - Adhyanti; Elvyrah Faisal; Niralda Widya Santika Irfan; Abd. Farid Lewa (Jurnal Pengabdian Masyarakat: Svasta Harena, 2022)
Assessment of nutritional status is an important thing related to a person's level of health in order to prevent malnutrition and the risk of becoming undernourished. The tool that is often and commonly used to measure body circumference is a manual meter. This measuring tool is useful for measuring body circumferences such as upper arm circumference measurements for pregnant women, women of childbearing age (WUS) and adolescent girls, head circumference in infants, and abdominal circumference measurements for adult women and men. Measurement using a manual meter still takes a lot of time and is less practical. the purpose of this community service is to design and test the accuracy of digital body circumference measuring instruments. The method of this activity is the diffusion of science and technology to produce a digital body circumference measurement tool. The results of this activity indicate that the use of a digital body circumference measuring instrument has been successfully carried out and is used with a correlation coefficient value of > 0.6 so that the digital body circumference measuring instrument has good accuracy for measuring body circumference. The conclusion of this activity is that the digital measuring instrument has been successfully used and is declared accurate and can simplify and make it more practical when used in measurements.